2020
DOI: 10.1007/s00167-020-06057-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparable clinical outcomes using knotless and knot-tying anchors for arthroscopic capsulolabral repair in recurrent anterior glenohumeral instability at mean 5-year follow-up

Abstract: Purpose To compare rates of recurrent instability, revision surgery and functional outcomes following arthroscopic anterior capsulolabral repair for recurrent anterior instability using knot-tying versus knotless suture anchor techniques. Methods Patients who had undergone arthroscopic anterior labrum and capsular repair for recurrent anterior glenohumeral instability using knotless anchors were identiied. Those with minimum 2-year follow-up were matched (1:2) to knot-tying anchor repair patients. Rates of fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 29 publications
0
38
0
5
Order By: Relevance
“…[21][22][23][24] Some studies have reported superior outcomes using KSA, but the difference in these series did not reach statistical significance. 23,24 Absorbable anchors were introduced to reduce the complications of implant loosening, migration and articular damage. With absorption over time, they minimise the interference with further revision surgery.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…[21][22][23][24] Some studies have reported superior outcomes using KSA, but the difference in these series did not reach statistical significance. 23,24 Absorbable anchors were introduced to reduce the complications of implant loosening, migration and articular damage. With absorption over time, they minimise the interference with further revision surgery.…”
Section: Discussionmentioning
confidence: 89%
“…20 Clinical studies comparing ABR using TSA and KSA have generally revealed comparable outcomes in terms of functional outcomes, recurrence of instability, return to pre-injury level and restriction of range of motion, in particular ER. 21 24 Some studies have reported superior outcomes using KSA, but the difference in these series did not reach statistical significance. 23,24…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Knot configurations used in knot-tying repair included horizontal mattress, 8 sliding hangman's knot with alternating half-stitches, 9,10 and nonsliding Revo knot with alternating half-stitches. 11 Most knotless anchors used are PEEK (polyether ether ketone) anchors manufactured by Arthrex (Push-Lock) [8][9][10]12 or Depuy (Mitek Bioknotless). 11,13,14 Three case series on knotless repair used metallic knotless anchors manufactured by Depuy.…”
Section: Study Characteristicsmentioning
confidence: 99%